Upcycling of Wastewater Sludge Incineration Ash as a 3D Printing Technology Resource - Ki, Dongwon; Kang, Shin Young; Park, Kwang-Min (Frontiers in Sustainability, 2021)
Recycling of usable resources from wastes must be prioritized to adhere to the circular economy policy implemented worldwide. This study aims to use wastewater sludge incineration ash (WSIA), which is a by-product of wastewater sludge treatment processes, in the 3D printing industry as a sustainable material. First, we explored the stability of incinerated ash generated from a wastewater treatment facility in Seoul by evaluating its physical (water content, organic matter content, and particle size) and chemical (oxide compound composition) characteristics. Composition ratios of the predominant oxides of silicon (SiO2), aluminum (Al2O3), phosphorous (P2O5), iron (Fe2O3), and calcium (CaO) were stable for six months. This finding indicated the potential for the incinerated ash to be commercially viable as a powder-bed 3D printed geopolymer. We then examined the optimal ratio of admixtures between the incinerated ash and ultra rapid hardening cement and the following post-treatment process method as a curing stage. The composite material made with 25% WSIA exhibited stability during the curing stage using alkaline solutions, and its compressive strength and water absorption were in accordance with the values recommended by the Korean Standard for decorative concrete blocks (KS F 4038). Additionally, a geopolymer prototype with 25% incinerated ash was produced. To support efficient upcycling of WSIA, long-term environmental and functional monitoring of the final product, effects of incinerated ash particle sizes, and post-treatment process times were further investigated to reduce costs.